Frailty as a Predictor of Postoperative Morbidity and Mortality Following Liver Resection. Issue 4 (April 2021) - McKechnie, Tyler; Bao, Tyler; Fabbro, Matthew; Ruo, Leyo; Serrano, Pablo E.
Background: Liver resection is commonly performed among patients at risk of being frail. Frailty can be used to assess perioperative risk. Thus, we evaluated frailty as a predictor of postoperative complications following liver resection using a validated modified frailty index (mFI). Methods: A retrospective cohort of consecutive patients undergoing liver resection (2011-2018) were stratified according to the mFI and classified as the following: high (≥.27) and low mFI (<.27). The effect of mFI on postoperative complications (Clavien-Dindo) was evaluated using multiple logistic regression, expressed as odds ratios (OR) and 95% CI. Results: Of 409 patients, 58 (14%) had high mFI. There were no differences in type of liver resection (laparoscopic: 57% vs 55%, P = .766), number of segments resected (3 vs 4, P = .417), or operative time (257 vs 293 minutes, P = .097) between the high and low mFI groups, respectively. High mFI patients had a longer median length of hospital stay (9.5 vs 5 days, P < .001) and higher proportion of postoperative complications (79% vs 46%, P < .001), including minor complications (69% vs 42%, P < .001), major complications (50% vs 13%, P < .001), and 90-day postoperative mortality (12% vs 3.4%, P = .04). On multivariable analysis, longer operating time (OR 1.15, 95% CI, 1.03 to 1.27), higher number of segments resected (OR 1.43, 95% CI, 1.12 to 1.82), and high mFI (OR 6.74, 95% CI, 2.76 to 16.51) were independent predictors of major postoperative complications. Discussion: mFI predicts postoperative outcomes following liver resection and can be used as a risk stratification tool for patients being considered for surgery.